Training-intensity distribution during an Ironman season: relationship with competition performance - Muñoz, I.; Cejuela, R.; Seiler, S.; Larumbe, E.; Esteve-Lanao, J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To describe training loads during an Ironman training program based on intensity zones and observe training-performance relationships. Methods: Nine triathletes completed a program with the same periodization model aiming at participation in the same Ironman event. Before and during the study, subjects performed ramp-protocol tests, running, and cycling to determine aerobic (AeT) and anaerobic thresholds (AnT) through gas-exchange analysis. For swimming, subjects performed a graded lactate test to determine AeT and AnT. Training was subsequently controlled by heart rate (HR) during each training session over 18 wk. Training and the competition were both quantified based on the cumulative time spent in 3 intensity zones: zone 1 (low intensity; <AeT), zone 2 (moderate intensity; between AeT and AnT), and zone 3 (high intensity; >AnT). Results: Most of training time was spent in zone 1 (68% ± 14%), whereas the Ironman competition was primarily performed in zone 2 (59% ± 22%). Significant inverse correlations were found between both total training time and training time in zone 1 vs performance time in competition (r = -.69 and -.92, respectively). In contrast, there was a moderate positive correlation between total training time in zone 2 and performance time in competition (r = .53) and a strong positive correlation between percentage of total training time in zone 2 and performance time in competition (r = .94). Conclusions: While athletes perform with HR mainly in zone 2, better performances are associated with more training time spent in zone 1. A high amount of cycling training in zone 2 may contribute to poorer overall performance.